Is Qtc Interval Associated With Insulin Resistance in Metabolic Syndrome? - Aleksandra, Milovancev; Stokic, Edita; Plecas-Duric, Aleksandra; Popovic, Dorde; Ilincic, Branislava (Cardiology and Cardiovascular Medicine, 2016)
Background/Aims: Prolonged corrected QT interval (QTc) is related to ventricular malignant arrhythmia and increases the risk of sudden cardiac death. This study assesses the association between cardio metabolic abnormalities and length of the QTc interval in the Province of Vojvodina, a region with the highest prevalence of obesity in Serbia. Methods: The study involved 80 patients, 50 patients with metabolic syndrome (MetSy) and 30 healthy individuals. According to the Adult Treatment Panel III criteria we established the diagnosis of Metabolic syndrome. We performed anthropometric measurements (body height, body weight, and waist circumference), body fat mass, insulin resistance parameters and serum lipids estimation. Electrocardiograms were collected and QTc intervals calculated by the Bazett formula. Pearson Correlation was used to show the correlation between anthropometric and metabolic parameters and QTc interval duration. Results: QTc interval was significantly longer in Metabolic syndrome patients than in the control group (411.1 ± 35.72 vs. 390.95 ± 26.31 msec, p <0.05). The strongest correlation was found between the length of the Qtc interval and insulin resistance parameters. Metabolic syndrome components such as fasting insulin (p<0.01), and fasting HOMA-IR (p<0.01) was significantly associated with increased QTc interval length. In conclusion, this study demonstrates that prolongation of the QTc interval is associated with insulin resistance and Metabolic syndrome. QTc interval should be monitored very closely in patients with Metabolic syndrome because the prolonged Qtc interval is associated with impaired ventricular depolarization and poor cardiovascular outcomes.